In-hospital survival of adults with HIV-associated cryptococcal meningitis in Tanzania: A retrospective comparison of amphotericin B-based regimen and fluconazole monotherapy - Mlela Msongela; George Musiba; Juma A. Mohamed; Alphonce I. Marealle; Manase Kilonzi; Ritah F. Mutagonda (PLoS ONE, 2025)
Objective This study aimed to examine treatment modalities, outcomes, and factors associated with in-hospital survival among people with HIV (PHIV) diagnosed with cryptococcal meningitis (CM) in Tanzania. Methods This hospital-based cross-sectional study retrospectively reviewed records of PHIV admitted to medical wards at Dodoma and Singida Regional Referral Hospitals in Tanzania from July 2019 to June 2024. Data on socio-demographics, antiretroviral therapy (ART) status, CD4 count, treatment, and outcomes were extracted using a standardised data collection tool. The primary outcome was in-hospital survival (discharged alive vs died). Descriptive statistics summarised patient characteristics, and modified Poisson regression with robust variance estimated adjusted risk ratios (aRR) for factors associated with being discharged alive. Results A total of 159 PHIV with CM records were reviewed. Of these, 89 (56.0%) were aged 36–55 years, 89 (56.0%) were female, and 138 (86.8%) were in WHO clinical stage IV. Of 159 patients, 88 (55.3%) received fluconazole monotherapy. In-hospital mortality among CM patients was 65 (46.5%). Discharge alive occurred in 61/73 (83.6%) of those on amphotericin B–based regimens versus 13/66 (19.7%) on fluconazole monotherapy. Patients treated with amphotericin B–based regimens were four times more likely to be discharged alive compared to those on fluconazole monotherapy (aPR = 4.19, 95% CI: 2.46–7.16, p < 0.001). Conclusion CM remains a leading opportunistic infection causing high mortality among PHIV, with most patients managed using fluconazole monotherapy. In-hospital survival was significantly higher with amphotericin B–based regimens, highlighting the need to align practice with guideline recommendations. Further qualitative research is warranted to explore barriers to implementing recommended CM treatment.